Surgical repair of large adult Bochdalek hernia: case series and literature review - Abbastanira, Shahd; Almarzouqi, Omar; Al rawi, Sura; Kannas, Samah; Bashier, Sara; Mrayyan, Hala; Al Ozaibi, Labib (Frontiers in Surgery, 2026)
IntroductionBochdalek hernia is a rare congenital diaphragmatic defect, typically diagnosed in infancy. Adult presentation is uncommon, and management remains debated, particularly in asymptomatic cases. This report presents two adult cases successfully treated with surgical repair, contributing to the limited literature on adult Bochdalek hernias.Presentation of caseA 20-year-old male, with no prior medical history, was incidentally found to have a left posterolateral diaphragmatic defect (5 × 7 cm) containing small bowel, splenic flexure of the colon, and the left kidney. Laparoscopic repair was attempted but converted to open surgery due to limited visualization and tension. Postoperatively, he developed a left pneumothorax and pneumoperitoneum requiring chest tube placement and was discharged on day six. A 43-year-old female with previous gastric banding presented with recurrent nausea, vomiting, and abdominal pain. Imaging revealed a large left diaphragmatic hernia (12 × 6 cm) containing stomach and bowel segments. She underwent emergency open repair. Postoperative recovery was complicated by a minimal left pneumothorax, which resolved, and she was discharged on day nine.DiscussionAdult Bochdalek hernias are rare and may be discovered incidentally or present with acute symptoms. Surgical repair is recommended to prevent complications, and laparoscopic approaches may require conversion to open repair in cases of large defects or high tension.ConclusionEarly recognition and timely surgical intervention are crucial for adult Bochdalek hernia, even in asymptomatic patients. These cases highlight effective management strategies and enhance understanding of this rare adult presentation.